TRADISI UNGGAHAN SEBAGAI TRANSFORMASI AGAMA, SOSIAL, DAN BUDAYA (Studi Etnografi Komunitas Bonokeling di Desa Pekuncen Kecamatan Jatilawang Kabupaten Banyumas) - Nawawi Nawawi (IAIN Purwokerto, 2016)
Abstract: Unggahan tradition in a ritual that is unique and full of magical feel. Unggahan conducted at sites considered sacred and trusted local people can get closer to the Almighty. This ritual in understood as a form of preservation of cultural heritage. In the social and cultural context, unggahan can be used as a vehicle for social cohesion, a means of togetherness of community members. In a unggahan ritual procession, community members gathered togheter without any barriers in the class and social status. Unggahan centred in rural communities Bonokeling Pekuncen Jatilawang District of Banyumas. All members of the community, including â€œchild putuâ€ of the various regions, both in the district of the Banyumas, Cilacap, Banjarnegara, even in far away arears come together in Pekuncen. Unggahan also become a means of gathering the family and as well as a social, cultural, and religious transformation. Unggahan is an expression of piety society where a sense of mutual assistance, solidarity and togetherness become main patterns of this tradition. Keyword: Unggahan, Transformation, Religion, Social, Culture.